1995
DOI: 10.2105/ajph.85.4.494
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of contraception: a comparison of 15 methods.

Abstract: OBJECTIVES. The purpose of the study was to determine the clinical and economic impact of alternative contraceptive methods. METHODS. Direct medical costs (method use, side effects, and unintended pregnancies) associated with 15 contraceptive methods were modeled from the perspectives of a private payer and a publicly funded program. Cost data were drawn from a national claims database and MediCal. The main outcome measures included 1-year and 5-year costs and number of pregnancies avoided compared with use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
2
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(93 citation statements)
references
References 17 publications
3
85
2
3
Order By: Relevance
“…They have concluded that all the contraceptive strategies have been more effective and less costly than no method. [12] This fi nding differs from that in our study. In our study the comparator has been the top priority 'National family welfare program'.…”
Section: Discussioncontrasting
confidence: 99%
“…They have concluded that all the contraceptive strategies have been more effective and less costly than no method. [12] This fi nding differs from that in our study. In our study the comparator has been the top priority 'National family welfare program'.…”
Section: Discussioncontrasting
confidence: 99%
“…They also realized that IUDs were not as profitable as their less controversial oral contraceptive product lines [51]. As such, from 1983-1988 there were no IUDs on the market in the United States [52].…”
Section: Dalkon Shield Fall-outmentioning
confidence: 99%
“…The effect it has on the cervical mucus by thickening it may be beneficial as it protects against ascending upper genital tract infections. 17,18 Notwithstanding the high efficacy and other benefits of implants, the method requires a minor surgical procedure for both insertion and removal, and these are dependent on the health provider. In addition, they can be visible and palpable at the site of insertion and they do not protect against sexually transmitted infections.…”
Section: Introductionmentioning
confidence: 99%